2022
DOI: 10.3389/fpsyg.2022.814759
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors of the Entrepreneurial Performance of Undergraduates

Abstract: College students have gradually become the main force of entrepreneurship in mass entrepreneurship and innovation. However, their entrepreneurial performance was not as good as expected. We have carried out research to analyze the predictive factors of entrepreneurial performance of college students and put forward targeted suggestions, hoping to be helpful to improve their entrepreneurial performance of them. Based on questionnaire data obtained from 2,097 college student entrepreneurs, this study uses the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…Similarly, the study reveals a significant positive relationship between risk preference level and agri-entrepreneurship performance. The finding also supported by Arafat et al (2018), Shaowel et al (2022 and Adobor (2020) financial risk (interest) and business environment risk could increase agri-entrepreneurship performance. Adversary, Devkota et al (2022) claimed that 55.7% of the 21-30 age group farmers reported that unknown risk-taking provide the opportunities for agrientrepreneurship performance success.…”
Section: Inferential Analysissupporting
confidence: 76%
“…Similarly, the study reveals a significant positive relationship between risk preference level and agri-entrepreneurship performance. The finding also supported by Arafat et al (2018), Shaowel et al (2022 and Adobor (2020) financial risk (interest) and business environment risk could increase agri-entrepreneurship performance. Adversary, Devkota et al (2022) claimed that 55.7% of the 21-30 age group farmers reported that unknown risk-taking provide the opportunities for agrientrepreneurship performance success.…”
Section: Inferential Analysissupporting
confidence: 76%
“…Similarly, the study reveals a significant positive relationship between risk preference level and agri-entrepreneurship performance. The finding is also supported by Arafat et al (2018), Shaowel et al (2022) and Adobor (2020). Financial risk (interest) and business environment risk could increase agri-entrepreneurship performance.…”
Section: Discussionmentioning
confidence: 62%
“…According to Wang and Jiang (2021), learners should possess several entrepreneurial values. Six important values are considered when implementing entrepreneurship: independence, creativity, daring to take risks, action-oriented, leadership, and working hard (Agustina & Fauzia, 2021;Lubada et al, 2021;Shaowei et al, 2022).…”
Section: Figure 4 Open Unemployment Rate By Education Levelmentioning
confidence: 99%